In defense of legal positivism - Kramer, Matthew H. (Oxford University Press, 2003)
This book is an uncompromising defense of legal positivism that insists on the separability of law and morality. After distinguishing among three facets of morality, Kramer explores a variety of ways in which law has been perceived as integrally connected to each of those facets. The book concludes with a detailed discussion of the obligation to obey the law--a discussion that highlights the strengths of legal positivism in the domain of political philosophy as much as in the domain of jurisprudence